Replicating or Evolving? Highlighting the Tension between Organizational Fit and Diversity in Recruitment Processes - Hempel,Florian; Kadarusman,Verel Pranidino (2025)
In modern recruitment, organizations tend to face a persistent paradox: they must align candidates with existing cultural values while simultaneously promoting workforce diversity. This thesis investigates how HR professionals navigate the inherent tension between organizational fit and diversity within recruitment processes across multinational public and private organizations in Europe and Southeast Asia. Drawing on paradox theory as the central analytical lens, alongside fit theory and diversity management literature, the study conceptualizes this tension not as a binary trade-off, but as a dynamic and enduring paradox embedded in daily hiring decisions. The research is based on eleven semi-structured interviews with HR professionals directly involved in shaping recruitment strategy and execution. Using the Gioia Method, two interrelated empirical dimensions emerged: (1) organizational fit, while widely valued, is inconsistently defined and frequently used as a proxy for similarity, enabling both inclusion and subtle exclusion; and (2) the HR professionals–hiring manager relationship is a key site where competing priorities are negotiated, shaping how inclusion is either enacted or constrained in practice. Findings indicate that inclusive hiring is influenced not only by formal tools and policies but also by relational dynamics, power asymmetries, and contextual flexibility. HR professionals who were able to challenge narrow fit assumptions and co-create assessment criteria with managers had greater influence in aligning inclusion with strategic hiring goals. However, vague role boundaries, organizational inertia, and unexamined norms often limited these efforts. By reframing fit as a flexible and inclusive construct, the study contributes to a more practice-oriented understanding of how HR professionals act as agents of both cultural continuity and change.
Keywords: organizational fit; diversity; inclusive recruitment; paradox theory; HR professional– hiring manager collaboration; fit theory; diversity management; multinational organizations; Europe; Southeast Asia